Perancangan Strategi Segmentasi Calon Mahasiswa Menggunakan Metode CHAID (Chi-Squared Automatic Interaction Detection) Pada PADMI Universitas Telkom - Ardiansah Ardiansah; Sari Wulandari; Putra Fajar Alam (TeIKa, 2023)
One of the enormous sources of funds or income obtained by Private Universities (PTS) comes from tuition fees. Therefore, the number of students who register is an essential factor in determining the survival of the PTS. As one of the private universities in Indonesia, Telkom University seeks to increase the percentage of prospective students who continue registration. An action to elevate the desire of prospective students to continue registration is by implementing the right marketing strategy is intended to be made. As a part responsible for the new student registration process at Telkom University, PADMI Telkom University is currently developing an effective segmentation strategy, namely a marketing strategy in following the segment profile of prospective students. The research conducted through the CHAID method to design a segmentation strategy for prospective students. The results could be the foremost consideration in creating a marketing strategy developed by PADMI Telkom University by founding fourteen forthcoming student segments and eight proposed marketing strategies for each of the assembled prospective student segments.